Grammar efficacy and grammar performance: an exploratory study on Arabic learners - Mustapha, Nik Hanan; Mustapha, Nik Farhan (Mediterranean Center of Social and Educational Research, 2017)
Previous research has clearly documented that self-efficacy in language learning positively affects students’ performance in acquiring language skills. While much research has studied grammar efficacy indirectly as part of writing efficacy, none of these focuses on Arabic language learning. Considering the impact of self-efficacy on language learning, as well as the important role of grammar in Arabic learning, this study examines the relationship between grammar efficacy and grammar performance among students learning Arabic as a foreign language in Malaysian public universities. Specifically, it intends to determine the relationship between grammar efficacy and grammar performance among Arabic learners on three aspects: Correction of grammar errors, vocalization of words, and construction of sentences. Using a newly-developed questionnaire, 140 students majoring in Arabic language from a public university in Malaysia participated in the study. The questionnaire covers three important aspects in Arabic grammar learning: Correction of grammar errors, vocalization of words, and construction of sentences. This study showed a moderate correlation between grammar efficacy and grammar performance. Efficacy of sentence construction appeared to correlate the highest among the three aspects. Teachers’ awareness on the importance of heightening students perceived confidence in accomplishing grammar tasks will eventually promote better learning among students.